ANALISIS KETIMPANGAN SOSIAL TERHADAP PENCAPAIAN KOTA JAMBI MERAIH PERINGKAT UTAMA KOTA LAYAK ANAK STUDI KASUS PEKERJA ANAK - Syahputra, Chrisna; Melisa; Maulia, Siti Tiara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Jambi City was awarded the Main Category of the Child-Friendly City (Kota Layak Anak) designation in 2025. However, findings from observations, interviews, and documentation revealed that child labor remains prevalent in several areas of the city, indicating a discrepancy between policy achievements and the actual conditions experienced by children. This study aims to analyze the social inequality factors contributing to the persistence of child labor and to examine prevention efforts based on Max Weber’s theory of social stratification. The research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The findings indicate that child labor is influenced by family economic constraints, low parental educational attainment and social acceptance of child labor, as well as the suboptimal implementation of child protection policies. Prevention efforts include strengthening family economic resilience, increasing public awareness, and improving the implementation of child protection policies. The study concludes that the Child-Friendly City (Kota Layak Anak) designation has not yet fully reflected the substantive fulfillment of children's rights, highlighting the need for more effective and sustainable policy implementation.